2020
DOI: 10.1103/physrevresearch.2.032044
|View full text |Cite
|
Sign up to set email alerts
|

Exchange-driven all-optical magnetic switching in compensated 3d ferrimagnets

Abstract: Understanding how a single laser pulse can toggle magnetization in a compensated 3d ferrimagnet is a critical problem in ultrafast magnetism. To resolve it, we test single-shot all-optical switching of magnetization in Mn 2 Ru x Ga at different temperatures using femto-to picosecond pulses in the visible to far-infrared spectral ranges. The switching process is found to be independent of photon energy, but strongly dependent on both the pulse duration and sample temperature. Switching is disabled whenever the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 53 publications
(90 reference statements)
3
33
0
Order By: Relevance
“…This suggests that the use of nanoplasmon optics could make AOS technologically viable by making the attainable bit size comparable to that, for example, of heat-assisted magnetic recording 13 . The so far revealed mechanism behind AOS implies that it proceeds via fast and efficient demagnetization 6,[14][15][16] . Therefore, a crucial step towards achieving nanoplasmonic AOS is to follow the temporal evolution of the magnetization in response to plasmon nanoantenna-assisted resonant laser excitation.…”
Section: Introductionmentioning
confidence: 99%
“…This suggests that the use of nanoplasmon optics could make AOS technologically viable by making the attainable bit size comparable to that, for example, of heat-assisted magnetic recording 13 . The so far revealed mechanism behind AOS implies that it proceeds via fast and efficient demagnetization 6,[14][15][16] . Therefore, a crucial step towards achieving nanoplasmonic AOS is to follow the temporal evolution of the magnetization in response to plasmon nanoantenna-assisted resonant laser excitation.…”
Section: Introductionmentioning
confidence: 99%
“…The mechanism of single-shot AOS in Mn 2 RuGa is similar to that of GFC, although switching was realized only when the initial temperature was below the magnetization compensation temperature of Mn 2 RuGa. 45) Single-shot AOS is of purely thermal origin; therefore, magnetization switching can be induced by ultrashort electrical pulses and has garnered significant attention for future ultrafast spintronics devices. Magnetization switching triggered by electrical pulses has been reported in several studies.…”
Section: Perspectivesmentioning
confidence: 99%
“…30,[32][33][34][35][36][37][38][39] Single-shot AOS of GFC is mediated by the transient ferromagnetic state owing to the angular momentum transfer between the two sublattices. 40,41) Although several studies have demonstrated single-shot AOS in Tb-based RE-TM system such as TbFeCo alloy, 42) [Tb=Co] multilayer 43) and ferrimagnetic Heusler alloy Mn 2 Ru x Ga, 44,45) single-shot AOS has been primarily inves- tigated using Gd-based materials including synthetic ferrimagnets such as Co=Gd. [46][47][48] Whereas many studies on single-shot AOS have been performed on ferrimagnetic thin films, single-shot AOS for FMs has been considered difficult.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The technological potential of this discovery was quickly recognised, leading to proof-of-concept experiments in connection with information storage [2][3][4] . Such laser-driven magnetisation dynamics has also been explored in bulk rare-earth ferromagnets 5 , in ferrimagnets 2,[6][7][8][9][10][11][12][13] , and in ferromagnetic thin films 3,[14][15][16][17][18][19][20] . The underlying physical picture is not yet fully understood, given the diversity of mechanisms that can contribute to or influence the dynamics on distinct or overlapping time scales [21][22][23] .…”
Section: Introductionmentioning
confidence: 99%